Monitoring Kadar Oksigen Pasien COVID-19 Untuk Isolasi Mandiri Berbasis IoT: Monitoring Oxygen Levels of COVID-19 Patients for IoT-Based Self-Isolation - Azzah Rowani, Eka; Erwanto, Danang; Widhining Kusumastutie, Diah Arie (Jurnal Ilmiah Sistem Informasi, 2022)
Corona virus or commonly known as COVID-19, where the virus can be transmitted by animals or by humans, with symptoms such as a high fever that can reach 37.7℃ or more, or low blood oxygen levels and handling cases of the covid- 19 virus has been pursued properly. With direct treatment by doctors, treatment in hospitals to self-isolation treatment and with the application of self-isolation for covid-19 patients, it is hoped that they can always see the condition of body temperature and oxygen levels in the blood. This study, the method of checking the number of heart beats of isoman patients and the amount of oxygen in the patient's body was developed by connecting the device to the IOT Telegram, which for the microcontroller used is Wemos D1minilite and with this development it is hoped that it can help the front group to overcome COVID-19 to always be able to help patients who are running isoman. The results of the testing of the tools made obtained a data success of 99.71% by comparing the results of the two tools, namely a tool made by researchers with an oximeter, and in these results obtained a data error value of 0.29% of the total data of 20 isoman patients. The data used were taken from COVID-19 patients who were self-isolating, and there were some patients whose test results were below the specified parameters.